The focal mechanical properties of normal and diseased porcine aortic valve tissue measured by a novel microindentation device. (March 2021) - Maleki, Hoda; Doyle, Matthew G.; Chehade, Moussa; Liu, Qian; Simmons, Craig A.
Abstract: Cells sense and respond to the heterogeneous mechanical properties of their tissue microenvironment, with implications for the development of many diseases, including cancer, fibrosis, and aortic valve disease. Characterization of tissue mechanical heterogeneity on cellular length scales of tens of micrometers is thus important for understanding disease mechanobiology. In this study, we developed a low-cost bench-top microindentation system to readily map focal microscale soft tissue mechanical properties. The device was validated by comparison with atomic force microscopy nanoindentation of polyacrylamide gels. To demonstrate its utility, the device was used to measure the focal microscale elastic moduli of normal and diseased porcine aortic valve leaflet tissue. Consistent with previous studies, the fibrosa layer of intact leaflets was found to be 1.91-fold stiffer than the ventricularis layer, with both layers exhibiting significant heterogeneity in focal elastic moduli. For the first time, the microscale compressive moduli of focal proteoglycan-rich lesions in the fibrosa of early diseased porcine aortic valve leaflets were measured and found to be 2.44-fold softer than those of normal tissue. These data provide new insights into the tissue micromechanical environment in valvular disease and demonstrate the utility of the microindentation device for facile measurement of the focal mechanical properties of soft tissues.